2015
DOI: 10.1115/1.4029602
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Low Concentration Sand Transport in Multiphase Air–Water Horizontal Pipelines

Abstract: The ultimate goal o f this work is to determine the minimum flow rates necessary fo r effec tive transport o f sand in a pipeline carrying multiphase flow. In order to achieve this goal, an experimental study is performed in a horizontal pipeline using water and air as carrier fluids. In this study, successful transport o f sand is defined as the minimum flow rates of water and air at which all sand grains continue to move along in the pipe. The obtained data cover a wide range o f lic/uid and gas flow rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
6
19
0
Order By: Relevance
“…As mentioned before, this study is the first study that reports experimental data regarding particle transport in very low liquid flow rates. The previous experimental study performed by the authors (Najmi et al, 2015a) reported experimental data for sand transport in stratified flow for minimum liquid velocities of 0.06 m/s and 0.02 m/s for 0.1 and 0.05 m diameter pipe, respectively. Therefore the experimental data presented in the current study with maximum liquid flow velocity of 0.02 and 0.03 m/s for 0.1 and 0.05 m diameter pipe, respectively, provides a wide range of operating conditions for sand transport in multiphase flows.…”
Section: Methodsmentioning
confidence: 97%
“…As mentioned before, this study is the first study that reports experimental data regarding particle transport in very low liquid flow rates. The previous experimental study performed by the authors (Najmi et al, 2015a) reported experimental data for sand transport in stratified flow for minimum liquid velocities of 0.06 m/s and 0.02 m/s for 0.1 and 0.05 m diameter pipe, respectively. Therefore the experimental data presented in the current study with maximum liquid flow velocity of 0.02 and 0.03 m/s for 0.1 and 0.05 m diameter pipe, respectively, provides a wide range of operating conditions for sand transport in multiphase flows.…”
Section: Methodsmentioning
confidence: 97%
“…The fluids used were air and either water (ρ L ¼998 kg/m 3 , μ L ¼1.0 cP, σ ¼72 dynes/cm) or water mixed with Carboxy Methyl Cellulose (CMC) (ρ L ¼ 998 kg/m 3 , μ L ¼ 10 cP, σ ¼ 70 dynes/cm) to increase the liquid viscosity. According to King et al (2001) and Najmi et al (2015), waterþ CMC solutions exhibit Newtonian behavior. The viscosity of the liquid was measured using a Hydramotion Viscolite 700 portable viscometer.…”
Section: Flow Facilitymentioning
confidence: 98%
“…This causes the flow to become unstable, and the pipe will eventually clog. Partial pipeline blockages may lead to erosion, corrosion and local velocity increase (Najmi et al 2015). Plugging results from transporting slurries at velocities lower than the deposition velocity (Ibarra et al 2014;Najmi et al 2015;Salama 2000;King et al 2001;McLaury et al 2011;Al-lababidi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Solid particle distribution in pipelines is dictated by carrier fluid properties, solid properties, flow geometry and flow conditions such as velocity (Poloski et al 2009a, b;Yokuda et al 2009;Turian et al 1987;Ibarra et al 2014;Najmi et al 2015;Salama 2000;King et al 2001;McLaury et al 2011;Al-lababidi et al 2012;Ozbayoglu 2002;Gillies et al 2007;Rensing et al 2008;and Ma and Zhang 2008). Several flow regimes have been proposed by different researchers including Durand (1953), Newitt et al (1955), Turian et al (1987), Turian and Yuan (1977), Doron and Barnea (1996), Peysson (2004) and most recently (Ramsdell and Miedema 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation